2018
DOI: 10.1021/acsami.8b13173
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion in Ferroelectric Switching Performance of Polycrystalline Hf0.5Zr0.5O2 Thin Films

Abstract: Interests in nanoscale integrated ferroelectric devices using doped HfO2-based thin films are actively reviving in academia and industry. The main driving force for the formation of the metastable non-centrosymmetric ferroelectric phase is considered to be the interface/grain boundary energy effect of the small grains in polycrystalline configuration. These small grains, however, can invoke unfavorable material properties, such as nonuniform switching performance. This study provides an in-depth understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 64 publications
4
35
1
Order By: Relevance
“…Various defects, such as oxygen vacancies, charged defects, depletion layers, interfacial defects, other structural phases, and domain orientations, can be regarded as disorders. Therefore, the annihilation of the disorder can be attributed to the redistribution of oxygen vacancies or charged defects, a decrease in the depletion layer or interfacial defects, and improved uniformity of the structural phase or domain orientation. ,, Figure illustrates how the t 1 value increased after the wake-up process. The mean value of the characteristic switching time t 1 can be controlled by the degree of disorder as this governs the domain-wall velocity, the time needed for nucleation, and the average ferroelectric domain size. , During the wake-up process, the reduction in local fields produced by charged defects increases the time required for nucleation and the average domain size via domain-wall motion. , The local fields can induce a reduction in nucleation bias .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various defects, such as oxygen vacancies, charged defects, depletion layers, interfacial defects, other structural phases, and domain orientations, can be regarded as disorders. Therefore, the annihilation of the disorder can be attributed to the redistribution of oxygen vacancies or charged defects, a decrease in the depletion layer or interfacial defects, and improved uniformity of the structural phase or domain orientation. ,, Figure illustrates how the t 1 value increased after the wake-up process. The mean value of the characteristic switching time t 1 can be controlled by the degree of disorder as this governs the domain-wall velocity, the time needed for nucleation, and the average ferroelectric domain size. , During the wake-up process, the reduction in local fields produced by charged defects increases the time required for nucleation and the average domain size via domain-wall motion. , The local fields can induce a reduction in nucleation bias .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, there have been many studies on the ferroelectric polarization-switching kinetics of HfO 2 thin films doped with various dopants, such as Si, La, Al, and Zr. The characteristic features of NLS in HfO 2 , such as the nucleation rate and critical nucleation number for domain switching, have been reported in ferroelectric domain-switching dynamics investigations. These reports showed that ferroelectric domain switching in HfO 2 thin films is heavily influenced by the inhomogeneous distribution of the local field. , The nonuniform, localized built-in field results in domain pinning and a broad distribution of the characteristic switching time. However, the class of disorders in ferroelectric HfO 2 thin films is not well understood, and further study is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 4(a)-(c) show that by increasing the Si doping in HfO 2 , the switching transition becomes less steep and the number of intermediate V T states increases, although the same write pulsing scheme is used. This has been explained by an enhanced switching dispersion in the FE layer that originates from the increased amount of non-FE phase in the HfO 2 film [64] as the dopant content is increased.…”
Section: Fefet As a Synapsementioning
confidence: 99%
“…[ 67 ] Due to the much thinner film thickness of HfO 2 ‐based FE films compared with conventional FE film, the inhomogeneous field model (IFM) has recently been suggested. [ 68,69 ] All of these models describe the kinetic process of FE polarization switching, which is relevant to the dynamic process of ERS and PGM of FeFET. A quantitative description of the switching dynamics requires 2D modeling of the time‐dependent charge – voltage relationship across the electrode area.…”
Section: Fundamentals Of Fe Film and Fefet Operationmentioning
confidence: 99%